2004
DOI: 10.1002/neu.20031
|View full text |Cite
|
Sign up to set email alerts
|

Pruning of motor neuron branches establishes the DLM innervation pattern in Drosophila

Abstract: During the Drosophila life-cycle two sets of neuromuscular junctions are generated: the embryonic/larval NMJs develop during the first half, followed by the period of metamorphosis during which the adult counterpart is generated. Development of the adult innervation pattern is preceded by a withdrawal of larval NMJs, which occurs at the onset of metamorphosis, and is followed by adult-specific motor neuron outgrowth to innervate the newly developing adult fibers. Establishment of the adult innervation pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 59 publications
(69 reference statements)
0
39
1
Order By: Relevance
“…In the present study, comparison of glutamatergic DLM neuromuscular synapses and cerebellar CF-PC synapses revealed a surprising degree of conservation in the detailed properties of synaptic function. These synapses exhibit morphological similarities as well, including extensive branching of axons and spatial isolation of active zones (34,52,53). Initial characterization of short-term depression at CF-PC synapses has been followed by a series of studies progressively defining the underlying factors in greater detail (7,9,10).…”
Section: In Vivo Function For Nsf In Maintaining Active Zone T-snaresmentioning
confidence: 99%
“…In the present study, comparison of glutamatergic DLM neuromuscular synapses and cerebellar CF-PC synapses revealed a surprising degree of conservation in the detailed properties of synaptic function. These synapses exhibit morphological similarities as well, including extensive branching of axons and spatial isolation of active zones (34,52,53). Initial characterization of short-term depression at CF-PC synapses has been followed by a series of studies progressively defining the underlying factors in greater detail (7,9,10).…”
Section: In Vivo Function For Nsf In Maintaining Active Zone T-snaresmentioning
confidence: 99%
“…The neuromuscular junction (NMJ) of Drosophila, a structure formed by the terminals of motor neurons on somatic muscles, has turned out to be perfectly suited for studies of neuronal plasticity (Johansen et al 1989;Keshishian and Chiba 1993;Fernandes and Keshishian 1995;Hebbar and Fernandes 2004;Ruiz-Cañada and Budnik 2006a, b). In Drosophila and other insects, NMJs are formed in the embryo, grow rapidly in the larva, and are either eliminated or reorganized during metamorphosis to control adult muscles (Truman 1990;Levine et al 1995;Consoulas 2000;Consoulas et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…At the NMJ, Eaton et al have reported a situation where the pruning of small motor axon arbors proceeds by retraction (Eaton et al 2002). Since pruning at the Drosophila NMJ is a simultaneous event involving synapse proliferation and synaptic regression (Eaton et al 2002;Hebbar & Fernandes 2004), it seems less likely to be regulated by hormonal signalling events. Furthermore, unlike g-MB pruning, where the fragmentation of the axon occurs without a directional preference, motor axon retraction at the Drosophila NMJ begins with the sequential disassembly of the presynaptic components of the axon prior to axon withdrawal.…”
Section: Axon Pruning: the Remodelling Of Axons During Neurogenesismentioning
confidence: 99%
“…At the Drosophila NMJ, a rapid disassembly of synapses and the retraction of axonal arbors occur concurrently with a proliferative phase of synaptic growth (Eaton et al 2002;Hebbar & Fernandes 2004). Eaton and colleagues developed an elegant assay to detect the small-scale pruning events.…”
Section: Axon Pruning: the Remodelling Of Axons During Neurogenesismentioning
confidence: 99%